Intelligent transport systems and travel behaviour : 13th Scientific and Technical Conference "Transport Systems. Theory and Practice 2016", Katowice, Poland, September 19-21, 2016 : selected papers /: 13th Scientific and Technical Conference "Transport Systems. Theory and Practice 2016", Katowice, Poland, September 19-21, 2016 : selected papers. ([2017]) - Unknown
No abstract available